A REVIEW ON IN VIVO AND IN VITRO EXPERIMENTAL MODELS TO INVESTIGATE THE ANTI-INFLAMMATORY ACTIVITY OF HERBAL EXTRACTS - Kabir, Inayat; Ansari, Imtiyaz (Asian Journal of Pharmaceutical and Clinical Research, 2018)
The article emphasizes the anti-inflammatory effects of herbal extracts on different experimental models that are repeatedly used to test the in vivo anti-inflammatory activity of herbal components. Edema, granuloma and arthritis models are used to test the anti-inflammatory activity of plant extracts whereas formalin or acetic acid-induced writhing test and hot plate methods are the most repeatedly used to evaluate anti-nociceptive potentials of the herbal extracts. Although adjuvant-induced and collagen-induced arthritis models are also quite efficient, they have been used seldom to evaluate anti-inflammatory tendencies of the herbs. Here, we suggest a double positive reference model using both steroid and nonsteroidal anti-inflammatory drugs at the same time, instead of using only one of them either.